Role of hepatitis B virus non-structural protein HBx on HBV replication, interferon signaling, and hepatocarcinogenesis - Wang, Fei; Song, Hongxiao; Xu, Fengchao; Xu, Jing; Wang, Le; Yang, Fan; Zhu, Yujia; Tan, Guangyun (Frontiers in Microbiology, 2023)
Hepatitis B, a global health concern caused by the hepatitis B virus (HBV), infects nearly 2 billion individuals worldwide, as reported by the World Health Organization (WHO). HBV, a hepatotropic DNA virus, predominantly targets and replicates within hepatocytes. Those carrying the virus are at increased risk of liver cirrhosis and hepatocellular carcinoma, resulting in nearly 900,000 fatalities annually. The HBV X protein (HBx), encoded by the virus's open reading frame x, plays a key role in its virulence. This protein is integral to viral replication, immune modulation, and liver cancer progression. Despite its significance, the precise molecular mechanisms underlying HBx remain elusive. This review investigates the HBx protein's roles in HBV replication, interferon signaling regulation, and hepatocellular carcinoma progression. By understanding the complex interactions between the virus and its host mediated by HBx, we aim to establish a solid foundation for future research and the development of HBx-targeted therapeutics.